Implementation Of Receiving The Teachings Of The Word Of God Based On James 1:19-21 For Class V Christian Learners At SD Budya Wacana I Yogyakarta - Rosalia Claudia Peo; Eudia Angelia Ika Agustin; Paulus Sentot Purwoko (Sekolah Tinggi Teologi Kadesi Yogyakarta, 2022)
The goal of this study was to determine the extent to which fifth-grade students at SD Budya Wacana I Yogyakarta accepted the teachings of God's word based on James 1:19-21 during the academic year 2020/2021. This study employs quantitative research methods. Data is collected using a Likert scale and processed using several tests run through SPSS 20. Instrument validation and reliability tests, as well as normality tests, are used. To test the hypothesis, use the Confidence Interval formula with a 5% significance level, the regression significance test (Freg), and the one-way variance test (one-way ANOVA). The results showed that the magnitude of the contribution of accepting the teachings of God's Word with the implementation of becoming doers of the word based on James 1:19-27 For fifth-grade students at SD Budya Wacana I Academic Year 2020/2021 (Y), the regression equation Y = b + b1D1, Y = 9.636 + 1.651 D1, with a calculated F coefficient of 329.830 and a P-value of 0.000, These results indicate that the regression equation is very significant or very meaningful. The value of the correlation coefficient (ry1) between receiving the teachings of God's Word and the implementation of being a doer of the word based on James 1:19-27 For fifth-grade students at SD Budya Wacana I, Academic Year 2020/2021 (Y) of 0.934, with a positive relationship, and the influence in the category is very strong.